Urinary excretion of epidermal growth factor and rapid loss of kidney function. Issue 10 (17th October 2020) - Norvik, Jon Viljar; Harskamp, Laura R; Nair, Viji; Shedden, Kerby; Solbu, Marit D; Eriksen, Bjørn O; Kretzler, Matthias; Gansevoort, Ron T; Ju, Wenjun; Melsom, Toralf
Abstract: Background: Lower urinary excretion of the kidney tubule–specific biomarker epidermal growth factor (uEGF) is associated with increased risk of renal function [glomerular filtration rate (GFR)] loss in diabetes and in patients with established chronic kidney disease (CKD). We investigated whether uEGF is associated with rapid GFR decline or incident CKD in the general population. Methods: Subjects without CKD or diabetes were recruited from the general population in Tromso, Norway [Renal Iohexol Clearance Survey (RENIS); N  = 1249] and Groningen, the Netherlands [Prevention of REnal and Vascular END-stage disease (PREVEND); N  = 4534], with a median follow-up of 5.6 and 7.4 years, respectively. GFR was measured by iohexol clearance in the RENIS and estimated using the CKD Epidemiology Collaboration creatinine–cystatin C equation in the PREVEND study. Rapid GFR decline was defined as an annual GFR loss >3.0 mL/min/1.73 m 2 and in sensitivity analyses as subjects with the 10% steepest GFR slope within each cohort. Results: Lower baseline uEGF excretion was associated with rapid GFR loss in both cohorts {RENIS, odds ratio [OR] per 1 μg/mmol lower uEGF 1.42 [95% confidence interval (CI) 1.06–1.91], P = 0.02; PREVEND, OR 1.29 [95% CI 1.10–1.53], P < 0.01}, adjusted for baseline GFR, albumin:creatinine ratio and conventional CKD risk factors. Similar results were obtained using the outcome of the 10% steepest GFR slope in each cohort. Lower uEGF levels were associated with incident CKD in the combined analysis of both cohorts. Conclusions: Lower uEGF levels are associated with increased risk of rapid GFR loss and incident CKD in the general population. This finding, together with previous findings in CKD and high-risk populations, supports that uEGF may serve as a broadly applicable biomarker representing the tubular component of the current glomerulus-centric clinical risk assessment system. Graphical Abstract: